Cellulose composite structures – by design - Winkworth-Smith, Charles G. (2015)
The aim of the work presented in this thesis was to investigate different mechanical and chemical pre-treatments which can dramatically change the properties of native cellulose and add alternative routes to structure formation. Ball milled cellulose, which had a reduced crystallinity, degree of polymerisation and degradation temperature, was rehydrated in excess water resulting in recrystallisation. Fully amorphous samples recrystallised to the more thermodynamically stable type II polymorphic crystal structure. Flash differential scanning calorimetry (DSC), which allows thermal transitions to be scanned at much higher rates than conventional DSC, was able to register a glass transition temperature for amorphous cellulose. The next stage of the study focussed on the production of freeze dried galactomannan foams. Cellulose fibres provided reinforcement to the foams. The level of reinforcement was related to fibre content, size, crystallinity and surface roughness. Microfibrillated cellulose (MFC) provided the greatest reinforcement due to its much higher surface area and fibrillated structure. Extrusion was found to be a useful alternative to homogenisation for the production of MFC and to create foams using alternative processing to the freeze drying routes.